Understanding Assessment in Counselling and Psychotherapy / Counselling and Psychotherapy Practice - Bager-Charleson Sofie; Claringbull Norman; Van Rijn Biljana (Learning Matters, 2011)
This timely and accessible book offers students and trainees a thorough guide to clinical assessment. Foreword, Acknowledgements, Introduction, The Role of the Assessor in Private Practice, ''Diagnosing'' Problems, Treatment - Illuminating Shaded Areas?, Assessment in Organizations: An Overview, Conducting an Assessment, Appendix 1: Initial Assessment Form Used by the Metanoia Counselling and Psychotherapy Practice, References, Index.